Cell mechanotactic and cytotoxic response to zinc oxide nanorods depends on substrate stiffness. Issue 6 (6th October 2016) - Palamà, I. E.; D'Amone, S.; Arcadio, V.; Biasiucci, M.; Mezzi, A.; Cortese, B.
Graphical Abstract: Abstract: Bio-nanomaterials offer promise in the field of tissue engineering. Specifically, environmental cues such as the material chemistry, topography and rigidity of the surface to which cells adhere to, can alter and dictate cell shape, proliferation, migration, and gene expression. How deeply each factor (topographical, chemical and mechanical) drives cell response remains incompletely understood. To illustrate cell sensitivities to different factors, we herein present ZnO nanorods (ZnO-Nrds) coated on glass and polydimethylsiloxane (PDMS) substrates and analyzed cell viability and proliferation. The work presented here shows a clear response of various cell lines (mouse embryonic fibroblasts 3T3, human cervix carcinoma HeLa and human osteoblast-like cells MG63) to the rigidity of the underlying surface. The chemical counterpart, given by the presence of ZnO-Nrds, strongly reduced the cell viability of all cell lines. However, the substrate underlying the ZnO coating impacted cell spreading and viability. The substrates exhibited a better ability to neglect cell attachment and proliferation with the ZnO coating and pro-apoptoticity specifically with the PDMS as the underlying substrate which exhibited a "softer" environment with respect to a glass substrate. The results also revealed that the few cells that adhered to the ZnO-Nrds on PDMS and glass showed a rounded morphology. On the basis of these observations, we can correlate common features of phenomenological cell response to chemotactic and durotactic cues. The work presented herein reinforces the response of cells to changes in substrate rigidity. These observations provide a foundation for a potentially promising approach to decrease cell adhesion and thus as an optimal substrate for different applications such as prosthesis design, tissue engineering, anti-bio fouling materials and diagnostics.